Pengaruh Sholat Dhuha terhadap Kecerdasaan Spiritual Siswa di Pondok Pesantren At-Taufiqurrahman - Arlina; Pane, Nova Emiliya; Sitorus, Wildan; Munazah, Azra; Koto, Hidayatul Fikri (Ikatan Da'i Indonesia, 2023)
The Prophet Muhammad SAW brought the perfect religion, namely Islam, for the benefit of mankind. The type of worship that has the highest level in Islam is prayer. In Islamic teachings, as we know, there are two types of prayers, namely fardhu and sunnah prayers. The aim of the study was to find out whether there is a relationship between the habit of performing the shuha prayer and spiritual intelligence by students at the At-taufiqurrahman Islamic Boarding School, is there an impact of implementing Duha prayer on spiritual intelligence. The research subjects were taken from teachers, students, some alumni from the At-taufiqurrahman Islamic boarding school. The method for collecting data is through interviews using one of the social media, namely WhatsApp. The results of this study indicate that the implementation of Duha prayer can increase spiritual intelligence and even intellectual intelligence of students at the At-taufiqurrahman Islamic boarding school, namely by growing good character, akhlakul karimah, having an attitude of helping each other, respecting each other, polite and courteous and easier to understand lessons so that it makes it easier for students students in carrying out learning activities.